Elemental analysis of caries-affected root dentin and artificially demineralized dentin - Young-Hye Sung; Ho-Hyun Son; Keewook Yi; Juhea Chang (Korean Academy of Conservative Dentistry, 2016)
Objectives This study aimed to analyze the mineral composition of naturally- and artificially-produced caries-affected root dentin and to determine the elemental incorporation of resin-modified glass ionomer (RMGI) into the demineralized dentin. Materials and Methods Box-formed cavities were prepared on buccal and lingual root surfaces of sound human premolars (n = 15). One cavity was exposed to a microbial caries model using a strain of Streptococcus mutans. The other cavity was subjected to a chemical model under pH cycling. Premolars and molars with root surface caries were used as a natural caries model (n = 15). Outer caries lesion was removed using a carbide bur and a hand excavator under a dyeing technique and restored with RMGI (FujiII LC, GC Corp.). The weight percentages of calcium (Ca), phosphate (P), and strontium (Sr) and the widths of demineralized dentin were determined by electron probe microanalysis and compared among the groups using ANOVA and Tukey test (p < 0.05). Results There was a pattern of demineralization in all models, as visualized with scanning electron microscopy. Artificial models induced greater losses of Ca and P and larger widths of demineralized dentin than did a natural caries model (p < 0.05). Sr was diffused into the demineralized dentin layer from RMGI. Conclusions Both microbial and chemical caries models produced similar patterns of mineral composition on the caries-affected dentin. However, the artificial lesions had a relatively larger extent of demineralization than did the natural lesions. RMGI was incorporated into the superficial layer of the caries-affected dentin.